Easy as riding a bike? Bicycling competence as (re)learning to negotiate space. Issue 2 (4th March 2022) - Sersli, Stephanie; Gislason, Maya; Scott, Nicholas; Winters, Meghan
ABSTRACT: Safety concerns, notably sharing road space with motor traffic, pose barriers for bicycling. To address safety concerns, bicycle courses are designed to provide skills and know-how for bicyclists to share road space with traffic. This paper used Social Practice Theory combined with a critical gender lens to examine the impact of a bicycle course for women living in Vancouver, Canada. We aimed to: 1) describe bicycling competences and associated materials and meanings; 2) compare bicycling competences at different stages of uptake and maintenance; and 3) identify gendering processes shaping bicycling practices. We conducted interviews with 32 women in the year following their participation in a bicycle course. Data collection and analysis were guided by interpretive description methodology. Participants described competences as skills for road positioning and route-finding, knowing formal and informal rules (laws, etiquette) to interact with other road users, and having strategies to minimise gender harassment. Regarding uptake and maintenance, women with opportunities to engage in bicycling cultivated competences more quickly. Those without suitable bicycles rarely rode; others described a virtuous circle where more time in the saddle led to greater confidence. Gendering processes shaped nearly all aspects of bicycling and included safekeeping (taking disproportionate personal responsibility for safety) and cultivating an assertive bodily comportment to take up space. We recommend that courses be augmented with support to acquire suitable bicycles, social opportunities for bicycling, continued investment in bicycle infrastructure, education for motorists, and discussion regarding etiquette between bicyclists.